Temperature effect on the structure and conformational fluctuations in two zinc knuckles from the mouse mammary tumor virus. (June 2018) - Nedjoua, Drici; Krallafa, Abdelghani Mohamed
Graphical abstract: Abstract: Zinc fingers are small protein domains in which zinc plays a structural role, contributing to the stability of the zinc–peptide complex. Zinc fingers are structurally diverse and are present in proteins that perform a broad range of functions in various cellular processes, such as replication and repair, transcription and translation, metabolism and signaling, cell proliferation, and apoptosis. Zinc fingers typically function as interaction modules and bind to a wide variety of compounds, such as nucleic acids, proteins, and small molecules. In this study, we investigated the structural properties, in solution, of the proximal and distal zinc knuckles of the nucleocapsid (NC) protein from the mouse mammary tumor virus (MMTV) (MMTV NC). For this purpose, we performed a series of molecular dynamics simulations in aqueous solution at 300 K, 333 K, and 348 K. The temperature effect was evaluated in terms of root mean square deviation of the backbone atoms and root mean square fluctuation of the coordinating residue atoms. The stability of the zinc coordination sphere was analyzed based upon the time profile of the interatomic distances between the zinc ions and the chelator atoms. The results indicate that the hydrophobic character of the proximal zinc finger is dominant at 333 K. The low mobility of the coordinating residues suggests that the strong electrostatic effect exerted by the zinc ion on its coordinating residues is not influenced by the increase in temperature. The evolution of the structural parameters of the coordination sphere of the distal zinc finger at 300 K gives us a reasonable picture of the unfolding pathway, as proposed by Bombarda and coworkers (Bombarda et al., 2005 ), which can predict the binding order of the four conserved ligand-binding residues. Our results support the conclusion that the structural features can vary significantly between the two zinc knuckles of MMTV NC.